Direct electrical injury to brachial plexus - Maksud Mubarak Devale; Gaurav Jatin Kadakia; Vicky Ghewarchand Jain; Rohit Prakash Munot (Indian Journal of Plastic Surgery)
Electrical current can cause neurological damage directly or by conversion to thermal energy. However, electrical injury causing isolated brachial plexus injury without cutaneous burns is extremely rare. We present a case of a 17-year-old boy who sustained accidental electrical injury to left upper extremity with no associated entry or exit wounds. Complete motor and sensory loss in upper limb were noted immediately after injury. Subsequently, the patient showed partial recovery in muscles around the shoulder and in ulnar nerve distribution at 6 months. However, there was no improvement in muscles supplied by musculocutaneous, median and radial nerves. On exploration at 6 months after trauma, injury to the infraclavicular plexus was identified. Reconstruction of musculocutaneous, median and radial nerves by means of sural nerve cable grafts was performed. The patient has shown excellent recovery in musculocutaneous nerve function with acceptable recovery of radial nerve function at 1-year post-injury.